Different histological subtypes of peripheral lung cancer based on emphysema distribution in patients with both airflow limitation and CT-determined emphysema. (February 2017) - Shin, Beomsu; Shin, Sumin; Chung, Myung Jin; Lee, Hyun; Koh, Won-Jung; Kim, Hojoong; Park, Hye Yun
Highlights: Different histological subtypes based on emphysema distribution. Squamous cell carcinoma in peripheral lung lesions with emphysematous areas. Adenocarcinoma in peripheral lung lesions without emphysematous areas. Abstract: The histological subtypes by peripheral tumor location remain uncharacterized in COPD patients with emphysema. We investigated histologic subtypes of peripheral lung cancers based on the context of heterogeneous emphysema distribution in patients with airflow limitation and CT-determined emphysema. A retrospective, cross-sectional study was conducted using data from 754 patients with airflow limitation and newly-diagnosed primary lung cancers from February 2013 to February 2015. Of these, 230 patients had emphysema, as determined by computed tomography software designed to quantify emphysema. Among the 230 patients, the most common subtype in central lesions (n = 84) was squamous cell carcinoma (SCC) (n = 64/84, 76%). Adenocarcinoma (ADC) was more frequently observed in peripheral lesions (n = 146) than central lesions (58/146 [40%] vs. 4/84 [5%], p < 0.001). In peripheral lesions, ADC was more frequently seen in areas without emphysema than emphysema areas (43/74 [58%] vs. 15/72 [21%], p < 0.001), while SCC was more frequently found in emphysema areas than areas without emphysema (44/72 [61%] vs. 13/74 [18%], p < 0.001). These associations persisted with adjustments for age, sex, smoking status and forced expiratory volume in 1 s. In patients with both airflow limitation and CT-determined emphysema, the main histological subtype of peripheral lung cancer was SCC in emphysema areas and ADC in areas without emphysema.